Outcrops of columnar andesite shaped by periglacial processes – Jersak Hills, King George Island, Antarctica - Migoń, Piotr; Strzelecki, Mateusz C. (Quaestiones Geographicae, 2024)
This paper is an inventory of cold-climate landforms present in the andesitic Jersak Hills on King George Island in maritime Antarctica. These landforms developed under distinctive rock control imposed by columnar jointing in andesite. Multiple distinct types of slopes – ranging from low-angle rock surfaces to steep cliffs – have formed according to the spacing and inclination of joints. Numerous joints in the rock mass facilitate efficient mechanical weathering, which has produced in situ regolith on summits, sorted scree slopes and less regular talus slopes. Debris is then transported downslope by solifluction, which acts concurrently with frost sorting, responsible for the origin of patterned ground, particularly stone stripes. Slope-channel coupling, however, is limited. The diversity of periglacial landforms associated with frost-induced degradation of bedrock outcrops has developed in a relatively short time interval following deglaciation approximately 7,000 years, as suggested by dating from localities nearby.